1979
DOI: 10.1007/bf00236771
|View full text |Cite
|
Sign up to set email alerts
|

The responses of magno- and parvocellular cells of the monkey's lateral geniculate body to moving stimuli

Abstract: The responses to moving stimuli of single cells in the parvo- and magnocellular layers (PCL and MCL) of the macaque lateral geniculate nucleus (LGN) have been studied. PCL cells respond with a monophasic increase or decrease in firing when a bar passes across the receptive field, according to the wavelength composition of the stimulus. MCL cells respond with a biphasic sequence of excitation and suppression or vice versa dependent on whether a cell is on-centre or off-centre and on stimulus contrast direction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…This axon was physiologically identified as monocular and transient, with an ON-center, type III receptive field that resembled units of the magnocelhdar geniculate laminae (Wiesel and Hubel, 1966;Dreher et al, 1976;Schiller and Malpeli, 1978;Lee et al, 1979). Vol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This axon was physiologically identified as monocular and transient, with an ON-center, type III receptive field that resembled units of the magnocelhdar geniculate laminae (Wiesel and Hubel, 1966;Dreher et al, 1976;Schiller and Malpeli, 1978;Lee et al, 1979). Vol.…”
Section: Resultsmentioning
confidence: 99%
“…Both techniques yielded satisfactory results. However, the latter provided direct identification of thalamic afferents and in addition enabled us to distinquish parvoand magnocellular afferents from one another on the basis of receptive field organization (Wiesel and Hubel, 1966;Sherman et al, 1976;Dreher et al, 1977;Schiller and Malpeli, 1978;Lee et al, 1979). These studies have been reported briefly (Blasdel et al, 1981;Blasdel and Lund, 1982a, b).…”
mentioning
confidence: 99%
“…The non-linear input to a Y cell allows it to respond to fine patterns but only in a way which enables the cell to signal that a fine pattern is present somewhere in its field but does not enable the cell to signal where the pattern is located. Thus, Y cells could act to gate the cortical analysis of fine patterns by their increased impulse activity when patterns are present in their receptive fields (Lennie, 1980a Lee, Creutzfeldt, & Elepfandt (1979) have pointed out similarities, in the response to moving stimuli, of monkey magnocellular neurones and cells from the A and Al layers of the cat's l.g.n., in agreement with the homology we have proposed above.…”
Section: Latency To Electrical Stimulationmentioning
confidence: 99%
“…A recent study based on the model [42] reported that well-defi ned LGN spike trains reduce the noise and elevate the response to the preferred stimulus. It is known that the relay cells are distributed nonrandomly in the LGN of cats and monkeys [43][44][45][46][47] . So the alignment of the receptive fields of relay cells in the LGN [1,5,7,8] could also …”
Section: Mr and Orientation Selectivitymentioning
confidence: 99%